Principles of anatomy & physiology - Tortora, Gerard J.; Derrickson, Bryan (Wiley, 2021)
"Welcome to your course in anatomy and physiology! Many of you are taking this course because you hope to pursue a career in one of the allied health fields or nursing. Or perhaps you are simply interested in learning more about your own body. Whatever your motivation, Principles of Anatomy and Physiology, 15th edition and WileyPLUS have all the content and tools that you need to successfully navigate what can be a very challenging course. Over the past fourteen editions of this text we have made every effort to provide you with an accurate, clearly written, and expertly illustrated presentation of the structure and function of the human body and to explore the practical and relevant applications of your knowledge to everyday life and career development. This fifteenth edition remains true to these goals. It distinguishes itself from prior editions with updated and new illustrations and enhanced digital online learning resources"--